Inequality of Opportunity for Education in Sudan: Results from Multiple Indicators Cluster Survey, 2014 - Ahmed, Huda (Advances in Social Sciences Research Journal, 2020)
Inequality of opportunity (IoP) in education is widely addressed in the literature, with few, if any, in Sudan. This paper aims to measure IoP for educational attainment and school attendance in Sudan, using data collected by Multiple Indicators Cluster Survey (2014). Circumstance variables used were gender, household wealth, residential areas, head of household education, and region of residence. The study used ordered logistic and dissimilarity index to assess the ex-ante IoP and used the Human Opportunity Index for school attendance. The findings show that circumstance variables were responsible for more than half of the inequality. Household wealth accounted for the largest share, followed by the household head’s education level, then residential areas. The total coverage of school attendance was 51.3%, and about 14% of the chances were distributed unequally. The study recommended effective policies based on spatial redistribution of educational resources like teachers, books, schools, and to implement more comprehensive plans that integrate poverty reduction strategies.